KERANGKA KONSEPTUAL LEARNING TRAJECTORY SEBAGAI LANDASAN PENGEMBANGAN DEEP LEARNING DI SEKOLAH DASAR - Christie, Sabinus Rainer N; Nurul Laily Al Arsyadhi; Aris Badara; Sayidiman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Learning practices in elementary schools still tend to be oriented toward procedural mastery and surface-level learning outcomes, and therefore have not fully supported the realization of deep learning. One approach that has the potential to address this issue is the use of a learning trajectory framework, which serves as an instructional framework that considers the gradual and systematic development of students’ ways of thinking. This study aims to construct a conceptual learning trajectory framework grounded in the principles of deep learning for elementary school students. This study employs a qualitative approach using a literature review method, in which data were obtained from scholarly journal articles, academic books, and relevant documents discussing deep learning, learning trajectory, and elementary education. The data were analyzed using thematic analysis and content analysis to identify key concepts, instructional principles, and patterns of interrelationships among theories. The findings indicate that the integration of deep learning principles into a learning trajectory can be formulated through instructional stages that emphasize conceptual exploration, multiple representations, reflective discussion, and the strengthening of interconnections among concepts. The learning trajectory framework constructed in this study is expected to serve as a theoretical foundation and a conceptual guide for teachers in designing meaningful learning and supporting the development of deep learning among elementary school students